Computational investigation of air-fuel mixing system for natural gas powered motorcycle - Yeap, Beng Hi; Mustafa, Azeman; Yaacob, Zulkefli (2001)
The idea of incorporating a newly designed mixer into the existing carburetor of conventional motorcycle is the main objective of the development of natural gas motorcycle fuel system. In a bi-fuel motorcycle, the carburetor still plays a vital role in switching from fuel gas to petrol mode operation and vice-versa. The carburetor is the most important part of the fuel system of a motorcycle. All motorcycle engines carry variable venturi jet carburetors. The basic operation of the carburetor mainly depends on the restriction barrel called the venturi. When airflows through the venturi, its speed increases and its pressure decreases. Gasoline in its liquid state does not burn readily in the combustion chamber; only gas does. That is where the carburetor plays its part by atomizing the gasoline into mist in the air stream in order to burn efficiently in the combustion chamber. The decisive advantage of the prototype mixer now under development is that it does not require any atomizing process as the inlet fuel is in gas form. The main challenge focuses on designing a mixing device which mixes the supplied gas with the incoming air at an optimum ratio. In order to surmount the identified problems, the way fuel gas and air flow in the mixer have to be analyzed. In this case, the Computational Fluid Dynamics or CFD approach is applied in the design of the prototype mixer. The present work is aimed at further understanding of the air and fuel flow structure by performing CFD studies using a commercially available FLUENT code.